Institutional participation of the teachers at the general meeting - González Álvarez, María (Avances en Supervisión Educativa, 2019)
The aim of this paper is to learn, in the opinion of non-university teachers, about the importance of the teachers general meetingcompetences for the proper working of the school and the quality of the education, as well as the attention and dedication spent on these competences. . To carry out an exploratory analysis, we have written a specific protocol that was filled in by 2334 teachers from the different stages and /or studies and autonomous communities. The staff highly values the importance of these competences and the appropriation off he attention and dedication by the staff. There are differences regarding sex, ownership of the school and stages and studies. It is convenient to continue analyzing the importance given by the teaching staff to these competencie as well as their fulfillment. The initial and permanent training must consider the involvement of the teachers in the participative structure of the school.